Evaluation of the postharvest behavior of cape gooseberry from conventional and agroecological production systems - Guevara Collazos, Aura Jessica; Villagran Munar, Edwin Andres; Velasquez Ayala, Fabian Andres; Gonzalez Velandia, Kristle Danitza (Revista Mexicana de Ciencias Agrícolas, 2019)
The production of cape gooseberry (Physalis peruviana L.) in Colombia has a high socioeconomic interest due to its commercial potential and the large number of small-scale producers that make up the production system. The growing areas in Colombia are located on the cold thermal floors of the departments of Boyaca, Cundinamarca and Antioquia. Recently, in order to seek sustainability in agricultural production, agroecological production has had a growing increase in areas where this type of crop is established. Therefore, the objective of this research was to evaluate and compare the postharvest behaviors of cape gooseberry fruit, obtained under two agricultural production systems (conventional and agroecological) established under climatic conditions of the savanna of Bogota. The methodology consisted of the measurement and quantification of the main physicochemical variables: weight, equatorial diameter, firmness, pH, total soluble solids, acidity, respiration and weight loss during the different stages of maturity. These values were compared in reference to the provisions of NTC 4580. The results obtained for each property showed significant differences between each productive system and each state of maturity evaluated, finding a higher sensitivity to postharvest deterioration in fruits obtained through agroecological production.
Keywords: Physalis peruviana L.; acidity; firmness; maturity index